Evaluating the Effectiveness of the Santripreneur Program in Islamic Boarding School: A CIPP-Based Qualitative Assessment of Screenprinting Training - Yahya Mof; Willy Ramadan; Hilmi Mizani (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Pesantren (Islamic boarding schools) are not only centers for the transmission of religious education but also social institutions oriented towards community development. Globalization and the creative economy encourage Islamic boarding schools to develop entrepreneurship training as a relevant skill to equip their students. Several studies have shown that such training enhances creativity and character development, reduces the risk of unemployment, and provides social and economic value to the community. However, the majority of research continues to prioritize the implementation and impact of entrepreneurship training programs in pesantren. Empirical evaluation of these programs, particularly utilizing systematic evaluation models, remains underdeveloped. This study presents a comprehensive evaluation of a screen-printing training program within the Santripreneur program. These findings were obtained from a qualitative field study using the CIPP model to assess the screen printing training program at Almujahidin Marabahan. Data were collected through interviews, non-participant observation, and document analysis, and then analyzed descriptively using qualitative methods and source and method triangulation. These findings indicate that institutional alignment, openness to change, supportive resources, and practice-based training processes influence the successful and effective implementation of programs. In addition to producing tangible products, this program fosters entrepreneurial skills, positive attitudes, and entrepreneurial orientation among students. Empirically, this study demonstrates how the CIPP evaluation model can be used to understand and assess the integration of entrepreneurship training in the context of pesantren, thus expanding the literature on entrepreneurship education or training programs in religious educational institutions. Furthermore, this study provides practical recommendations for administrators and policymakers on designing programs that are needs-based, adequately resourced, and practice-based.